Cellular composition of the blood-brain barrier - Abbott, N. Joan (Henry Stewart Talks, 2008)
Sites of CNS barriers, Neurovascular unit, Blood-brain barrier (BBB) at brain capillary endothelium, Functions of BBB, Tight junctions, Pathways across the BBB, BBB biomarkers, Supporting cell types, Astrocytes and BBB induction, Pericytes, Microglia, Mast cells, Smooth muscle, BBB modulation, Heterogeneity, Changes in pathology
Archived at 2018/12/10